Pengaruh Display Produk dan Atmosfer Toko Terhadap Impuls Buying Pelanggan Koperasi Mahasiswa menggunakan Partial Least Square (PLS) - Ela Rolita Arifianti; Mochamad Rizqi Junianto; Fahrul Afiyas Suwignyo (Universitas Islam Raden Rahmat, Malang, 2024)
Article 33 paragraph (1) of the 1945 Constitution states that the Indonesian economy is structured as a joint business based on family principles and Cooperatives are one of the business entities in accordance with the intended economic structure. This research was conducted by distributing questionnaires to 70 respondents using the probability sampling method at Amanah student cooperative visitors using Partial Least Square (PLS 3.0) regression analysis to test the hypothesis to determine the effect of product displays and shop atmosphere on impulse buying of Amanah student cooperative visitors